A new bacterial tRNA enhances antibiotic production in Streptomyces by circumventing inefficient wobble base-pairing. Issue 12 (14th June 2022) - Chen, Ximing; Li, Shuyan; Zhang, Binglin; Sun, Haili; Wang, Jinxiu; Zhang, Wei; Meng, Wenbo; Chen, Tuo; Dyson, Paul; Liu, Guangxiu
Abstract: We report the discovery and functional characterization of a new bacterial tRNA species. The tRNA-Asp-AUC, from a fast-growing desert streptomycete, decodes GAU codons. In the absence of queuosine tRNA anticodon modification in streptomycetes, the new tRNA circumvents inefficient wobble base-pairing during translation. The tRNA, which is constitutively expressed, greatly enhances synthesis of 4 different antibiotics in the model mesophilic species Streptomyces coelicolor, including the product of a so-called cryptic pathway, and increases yields of medically-important antibiotics in other species. This can be rationalised due to increased expression of both pleiotropic and pathway-specific transcriptional activators of antibiotic biosynthesis whose genes generally possess one or more GAT codons; the frequency of this codon in these gene sets is significantly higher than the average for streptomycete genes. In addition, the tRNA enhances production of cobalamin, a precursor of S-adenosyl methionine, itself an essential cofactor for synthesis of many antibiotics. The results establish a new paradigm of inefficient wobble base-pairing involving GAU codons as an evolved strategy to regulate gene expression and, in particular, antibiotic biosynthesis. Circumventing this by expression of the new cognate tRNA offers a generic strategy to increase antibiotic yields and to expand the repertoire of much-needed new bioactive metabolites produced by these valuable bacteria.